Efficacy and safety of oral chelators in treatment of patients with Wilson disease - Weiss, Karl Heinz; Thurik, Florentine; Gotthardt, Daniel; Schäfer, Mark; Teufel-Schäfer, Ulrike; Wiegand, Franziska; Merle, Uta; Ferenci-Foerster, Daniela; Maieron, Andreas; Stauber, Rudolf; Zoller, Heinz; Schmidt, Hartmut H.; et al. (Clinical gastroenterology and hepatology, 2013)
Background & Aims - Wilson disease is a genetic copper storage disorder that causes hepatic and neurologic symptoms. Chelating agents (D-penicillamine, trientine) are used as first-line therapies for symptomatic patients, but there are few data from large cohorts. We assessed the safety of D-penicillamine and trientine therapy and outcomes of patients with Wilson disease. - Methods - We performed a retrospective analysis of data on 380 patients with Wilson disease from tertiary care centers in Germany and Austria, and 25 additional patients from the EUROWILSON registry. Chelator-based treatment regimens were analyzed for their effect on neurologic and hepatic symptoms and for adverse events that led to discontinuation of therapy (Kaplan-Meier estimation; data were collected for a mean of 13.3 y after therapy began). - Results - Changes in medication were common, resulting in analysis of 471 chelator monotherapies (326 patients receiving D-penicillamine and 141 receiving trientine). Nine of 326 patients treated with D-penicillamine and 3 of 141 patients given trientine underwent liver transplantation. Adverse events leading to discontinuation of treatment were more frequent among those receiving D-penicillamine than trientine (P = .039). Forty-eight months after therapy, hepatic deterioration was reported in only 4 of 333 patients treated initially with a chelating agent. Hepatic improvements were observed in more than 90%, and neurologic improvements were observed in more than 55%, of therapy-naive patients, and values did not differ significantly between treatments. However, neurologic deterioration was observed less frequently in patients given D-penicillamine first (6 of 295) than those given trientine first (4 of 38; P = .018). - Conclusions - Chelating agents are effective therapies for most patients with Wilson disease; D-penicillamine and trientine produce comparable outcomes, although D-penicillamine had a higher rate of adverse events. Few patients receiving chelation therapy had neurologic deterioration, which occurred more frequently in patients who received trientine.
Gesehen am 28.10.2021